Deep Learning Approaches for Speech Command Recognition in a Low Resource KUI Language - Kumar Nayak , Subrat; Kumar Nayak , Ajit; Mishra , Smitaprava; Mohanty , Prithviraj (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Over the time, computers can learn to understand speech from experience, thanks to incredible recent advances in deep learning algorithms. Speech command recognition becomes necessary when it comes to assisting disabled and impaired people, and executing hands-free activities in the sector of customer service and education. Speech recognition combines multiple disciplines from computer science to identify speech patterns. Identifying speech patterns help computers differentiate between various instructions for which it has been trained to perform. This research aims to implement speech command recognition technology into gaming, assisting players to play games in their native language. Speech recognition technology can be used as a way to engage with the various situations presented in video games, enabling a greater degree of immersion than what is possible through AR (Augmented Reality) and VR (Virtual Reality) technologies on their own. This research introduces various deep learning algorithms and their comparative analysis that can be applied to process speech commands, particularly in the KUI language. An in-depth analysis of the feature extraction techniques like Mel-frequency cepstral coefficient (MFCC) and deep learning algorithms such as Artificial Neural Networks (ANN), Recurrent Neural Networks (RNN), Convolutional Neural Networks (CNN) and Attention using LSTM have been presented. Various experiments are conducted to compare the performance metrics obtained from all the models applied.